2008
DOI: 10.1088/0953-4075/41/5/051001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for highly correlated electron dynamics in two-photon double ionization of helium

Abstract: Experiments using new sources of XUV pulses now tackle the difficult problem of few-photon direct double ionization of atoms. Despite its apparent simplicity, the fundamental process of two-photon direct double ionization of helium is far from being understood. Here, we use a time-dependent approach to study the process. Our results for the electron angular and energy distributions demonstrate that the dominant mechanism for double-electron escape involves a highly correlated electron motion. Angular correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 30 publications
(60 reference statements)
11
66
0
Order By: Relevance
“…Provided one of the electrons is emitted perpendicular to the laser polarization direction, it is found that the angular distribution of the other electron is characterized by three lobes. The results are similar to those recently reported for the corresponding process in the hydrogen negative ion [R. The problem of direct (nonsequential) two-photon double ionization of helium has been studied extensively in recent years, as exemplified by numerous theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and experimental [19][20][21][22][23][24] works. This breakup process is fundamental in the sense that it is one of the simplest processes in nature where electron correlations are exhibited, manifested by a rather complex interplay between the electrons.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Provided one of the electrons is emitted perpendicular to the laser polarization direction, it is found that the angular distribution of the other electron is characterized by three lobes. The results are similar to those recently reported for the corresponding process in the hydrogen negative ion [R. The problem of direct (nonsequential) two-photon double ionization of helium has been studied extensively in recent years, as exemplified by numerous theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and experimental [19][20][21][22][23][24] works. This breakup process is fundamental in the sense that it is one of the simplest processes in nature where electron correlations are exhibited, manifested by a rather complex interplay between the electrons.…”
supporting
confidence: 88%
“…1 clearly show that there is a strong backward-forward asymmetry. The bending of the left and right (symmetric) lobes has already been well documented in previous studies in He [5,11,13,[29][30][31], H − [25], and H 2 [26][27][28]32], and we will only comment briefly on this feature here. Assuming for the moment that the electrons absorb one photon each in the two-photon double ionization event, this would, to a zeroth-order approximation, give rise to a p-lobe structure (oriented along the laser polarization direction) in their respective angular distributions.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…5b) [56,57,63,69]. Unfortunately the momentum resolution of the present experiment (limited, among other factors, by space charge effects) does not allow us to reliably discriminate between these theoretical predictions.…”
Section: Recoil Ion Momentum Distributions For Double Ionization Of Hmentioning
confidence: 96%
“…According to a series of calculations [51,56,57,[63][64][65]68,101], a change of the shape of the energy distribution between both electrons should be expected. As discussed, e.g., in [63], for the photon energies of 40-45 eV equal energy sharing between both emitted electrons is needed in order to overcome the attraction of the nucleus and promote both electrons into the continuum (see Fig. 5a, taken from [63]), whereas as the photon energy approaches the SDI threshold (54.4 eV), the asymmetric energy sharing starts to dominate.…”
Section: Recoil Ion Momentum Distributions For Double Ionization Of Hmentioning
confidence: 99%